Gender-Based Analysis of Technical Efficiency in Rice Farming: A Case Study in Deli Serdang Regency - Jones T. Simatupang; Manaor Bismar Posman Nababan; Aditia Erick Cantona Simatupang (Jurnal AGRISEP, 2025)
Deli Serdang Regency is the foremost rice grower in North Sumatra Province. The disparity in input access between male and female producers is responsible for the low rice output in this region. This study aimed to assess the technical efficiency of rice cultivation among male and female producers and identify the inefficiency sources among rice farmers in Deli Serdang Regency. We employ a stochastic frontier methodology to assess the technical efficiency of rice cultivation and utilize a statistical difference test to evaluate efficiency disparities between the two cohorts of rice growers. Primary data was gathered from 400 farmers during the 2022 planting season. The study revealed that male rice growers exhibited greater efficiency than their female counterparts. Our findings indicate that male rice producers inadequately utilized labor, fertilizer, land, and pesticides, but female rice producers inadequately utilized labor and fertilizer. Factors contributing to inefficiency also included the frequency of extensions, experience with FBOs, agricultural expertise, and access to irrigation. Given that women dedicate considerable time to domestic responsibilities and child-rearing, local governments may establish extension and training initiatives—such as guidance on fertilizer application, pest management, and agricultural record-keeping—alongside health programs routinely administered at integrated service posts (Posyandu) and family welfare programs (PKK). Extension services are essential to enhance the knowledge and abilities of women rice farmers, hence improving technical efficiency, household welfare, and the sustainability of rice growing in Deli Serdang Regency.